Relationships Between Illicit Drug Use and Body Mass Index Among Adolescents. (February 2016) - Blackstone, Sarah R.; Herrmann, Lynn K.
Prior research has established associations between body mass index (BMI) and use of alcohol, tobacco, and marijuana. However, little research has been done investigating the relationship between other common illicit drugs and BMI trends. The present study investigated whether adolescents who reported using illicit drugs showed differences in BMI compared to peers who reported no drug use. There was a positive relationship between drug use and BMI as well as the number of drugs used and BMI. The results suggested that the positive relationship between the use of illicit drugs and BMI is largely due to smoking. Further research needs to ascertain whether smoking, illicit drug use, or both are among the first of many unhealthy behaviors that can subsequently lead to greater gains in BMI. Implications for health educators are discussed.